Deciphering the Role of CD36 in Gestational Diabetes Mellitus: Linking Fatty Acid Metabolism and Inflammation in Disease Pathogenesis - Huang L; Zhang T; Zhu Y; Lai X; Tao H; Xing Y; Li Z (Journal of Inflammation Research)
Li Huang,1– 3,* Tong Zhang,4,* Yuanyuan Zhu,5 Xueling Lai,6 Hualin Tao,1– 3 Yuhan Xing,5 Zhaoyinqian Li1– 3 1Department of Laboratory Medicine, the Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 2Sichuan Province Engineering Technology Research Center of Molecular Diagnosis of Clinical Diseases, Luzhou, Sichuan, People’s Republic of China; 3Molecular Diagnosis of Clinical Diseases Key Laboratory of Luzhou, Luzhou, Sichuan, People’s Republic of China; 4Department of Laboratory Medicine, Southwest Medical University, Luzhou, Sichuan, People’s Republic of China; 5School of Public Health (Shenzhen), Sun Yat-sen University, Shenzhen, Guangdong, People’s Republic of China; 6Shenzhen Guangming Maternal & Child Healthcare Hospital, Shenzhen, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhaoyinqian Li, Department of Laboratory Medicine, The Affiliated Hospital of Southwest Medical University, No. 25, Taiping Street, Jiangyang District, Luzhou, Sichuan, 646000, People’s Republic of China, Email lizhaoyinqian@swmu.edu.cn Yuhan Xing, School of Public Health (Shenzhen), Sun Yat-sen University, Shenzhen, 518107, People’s Republic of China, Email xingyh8@mail.sysu.edu.cnAbstract: Gestational diabetes mellitus (GDM) is one of the most common pregnancy complications which exerts detrimental effects on mothers and children. Emerging evidence has pointed to the important role of the fatty acid transporter protein CD36 in the pathogenesis of GDM. As a heavily glycosylated transmembrane protein, CD36 is widely expressed in diverse cell types, including placental trophoblasts, monocytes/macrophages, adipocytes, and pancreatic cells et al. CD36 plays a key role in lipid metabolism and signal transduction in the pathophysiological mechanism of GDM. The modified expression and functionality of CD36 may contribute to inflammation and oxidative stress in maternal tissues, interfere with insulin signaling, and subsequently influence maternal insulin sensitivity and fetal growth, increasing the risk for GDM. This review provides an overview of the current knowledge regarding the expression and function of CD36 in various tissues throughout pregnancy and explores how CD36 dysregulation can activate inflammatory pathways, worsen insulin resistance, and disrupt lipid metabolism, thereby complicating the necessary metabolic adjustments during pregnancy. Furthermore, the review delves into emerging therapeutic approaches targeting CD36 signaling to alleviate the impacts of GDM. Understanding the involvement of CD36 in GDM could yield crucial insights into its mechanisms and potential interventions for enhancing maternal and fetal health outcomes.Keywords: CD36, gestational diabetes mellitus, lipid metabolism, inflammation, insulin resistance, treatment